وکالت کی شرعی حیثیت - ڈاکٹر رشید احمد (الإيضاح, 2011)
Islam emphasizes on the establishment of a just society and it is the foremost duty of every Muslim to strive for that. A society can experience pease as long as justice prevails therein; it faces problems only when injusitce becomes order of the day. Justice or injustice is the byproduct of human behavior and interaction which at times lead to disputes and conflicts. Justice needs settlement of disputes and conflicts. For that matter it is necessary for judicial system to be in place. The present paper represents a humble attempt to explain and analyze judicial system as developed by the ummah.